Integration and Optimization of Digital Workflows in the Printing Industry - Zhang, Xiancang; Xia, Maohong; Chen, Xiaoyin; Liu, Lihuang; He, Jiangtao; Qiu, Xiaoying (International Journal of Social Sciences and Public Administration, 2024)
This paper comprehensively and deeply discusses the integration and optimization of digital workflow in the printing industry. By elaborating on the components of the digital workflow, such as document processing, color management, composition and layout, printing production control, and its key role in printing production, including significantly improving production efficiency, minimizing errors, accurately achieving color reproduction, and significantly enhancing production control. The application status of digital workflow in the industry is further analyzed, and prominent problems such as poor information flow and poor system compatibility are revealed. A series of integration and optimization strategies are put forward, including building a unified information management platform, carefully optimizing process design, and vigorously improving the digital level of equipment, etc., and with the help of practical cases, the remarkable results of optimization are vividly demonstrated. It aims to provide solid theoretical support and practical guidance for printing enterprises to achieve efficient and high-quality digital production goals.